A generalized model for smartphone adoption and use in an Arab context: A cross-country comparison. Issue 3 (3rd July 2018) - Ameen, Nisreen; Willis, Robert
ABSTRACT: The main aim of this research is to propose a conceptual model that explains the factors that can predict behavioral intention to use smartphones and the actual use of smartphones by young Arab consumers in three Arab countries: Iraq, Jordan, and the United Arab Emirates (U.A.E.). The findings indicate that the proposed extended model fits well in the three countries. The research provides information that can help policymakers and mobile companies.